ANALISIS KEPUASAN KERJA STAF ADMINISTRASI POLITEKNIK NEGERI SEMARANG - Puswiartika, Dhevy (Kreatif, 2014)
Abstract : This research intended to analyze job satisfaction of administration staffs on Politeknik Negeri Semarang. The data was collected by having job satisfaction scale from 67 respondents. The respondents were administration staffs on Politeknik Negeri Semarang. The job satisfaction scale adapted from the aspects of job satisfaction theory from Smith, Kendall,and Hullin. The data also collected by having interview with administration staffs and subordinate, also having observation of daily job condition. The sampling method of this research was cluster sampling. Statistic method which used to analyze the job satisfaction was parametric statistic technique. The results showed that level ofÂ  job satisfaction was âEnoughâ(59,7%). All aspect have balanced contribution to job satisfaction, included promotion chance, salary, partner, subordinate, and work characteristic. The enhancement process in one aspect will increase job satisfaction. On the other side, there were two aspects on lower rank in the job satisfaction analysis, included subordinate and promotion chance. Both of them were urgently to improved. Â  Keywords : job satisfaction, promotion chance, salary, partner, subordinate, work characteristic.